Empirical Validation of Qualitative Data: A Mixed Method Approach - Imran, Amina; Yusoff, Rosman Md (International Journal of Economics and Financial Issues, 2015)
Qualitative research method has been popular among practitioners for epistemological investigation into exposition of facts but generalization and validity of the qualitative design is still subject to question. The possible solution is to employ mixed method research design. The study suggests two stages sequential mixed method research designs that combine both the qualitative and quantitative nature of the data. Two stages mixed method research design provides liberty for collecting contextual information through analyzing qualitative data by using thematic networks. Further, these networks transform into scale to counter validity, reliability and generalization issues. Keywords: Mixed Method Research, Quantitative Data, Epistemological Investigations, Thematic Networks, Sequential Design JEL Classifications: C, C1